Adsorption and Complexing Properties of Silica Modified with β-Cyclodextrin - Belyakova, L.A.; Shvets, O.M. (Хімія, фізика та технологія поверхні, 2010)
The sorption of cadmium (II) cations on the surface of amorphous macroporous silicas chemically modified with β-cyclodextrin and its functional derivatives has been studied. It was shown that sorption of cadmium (II) follows the Frendlich isotherm for heterogeneous surface. Analysis of sorption kinetic curves in the framework of the Lagergren kinetic model for reactions of pseudo-first and pseudo-second order shows that two parallel processes take place on the surface of β-cyclodextrin-containing silicas. It has been proved that significant increasing of cadmium (II) nitrate sorption is a result of uncharged supramolecular structures formation on the surface of silicas modified with β-cyclodextrins. The chemical composition of these supramolecular structures correlates with the polarizability of functional substituents of β-cyclodextrins.